SPE Asia Pacific Oil and Gas Conference and Exhibition 1999
DOI: 10.2118/54381-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Polymer Producer TU-15A for MEOR Field Tests

Abstract: This paper was prepared for presentation at the 1999 SPE Asia Pacific Oil and Gas Conference and Exhibition held in Jakarta, Indonesia, 20–22 April 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Solutions were compared with commercial simulators or laboratory experiments and the results indicated that the model was able to determine the transport and metabolism of microorganisms in porous media, as well as to estimate the additional oil recovery due to MEOR processes. Sugai et al (2007) also presented a numerical model to analyse the MEOR mechanisms using laboratory data obtained by Sugai et al (1999) for the microorganism Clostridium sp. Their work was validated through the comparison of simulated data with experiments carried out in porous media.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Solutions were compared with commercial simulators or laboratory experiments and the results indicated that the model was able to determine the transport and metabolism of microorganisms in porous media, as well as to estimate the additional oil recovery due to MEOR processes. Sugai et al (2007) also presented a numerical model to analyse the MEOR mechanisms using laboratory data obtained by Sugai et al (1999) for the microorganism Clostridium sp. Their work was validated through the comparison of simulated data with experiments carried out in porous media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…-viscosity reduction by gas (CO 2 , H 2 , N 2 and CH 4 ) production or degradation of long-chain saturated hydrocarbons (Maure et al 2001;Strappa et al 2004;Bao et al 2009); -improvement of rock absolute permeability by the generation of acids that dissolve rock matrix (Yakimov et al 1997); -wettability modification and reduction of oil/water interfacial tension by surfactant production and bacterial presence (Sitnikov et al 1994;Zekri et al 2003;Almehaideb et al 2004;Kowalewski et al 2006;Soudmand-Asli et al 2007; Afrapoli et al 2009); -oil viscosity reduction by biosurfactants (Maure et al 2001;Karim et al 2001;Soudmand-Asli et al 2007); -selective plugging by microorganisms and biopolymers (Yakimov et al 1997;Mezzomo et al 2000;Soudmand-Asli et al 2007); -water viscosity increase due to biopolymers (Sugai et al 1999). The main objective of this paper is the modelling of a MEOR process in which microorganisms produce biopolymers that increase water viscosity and then improve reservoir sweep efficiency.…”
Section: Introductionmentioning
confidence: 99%